THE EFFECT OF PARENT EDUCATIONAL BACKGROUND ON STUDENT ACADEMIC PERFORMANCE OF ISLAMIC BOARDING SCHOOLS - Rosid Bahar; Heri Retnawati; Irfan Budiono (Universitas Islam Negeri Mataram, 2023)
Islamic boarding schools are institutions where students live who are not accompanied by their parents in their daily lives. The aim of this research is to determine the influence of parental education on the learning abilities of students living in Islamic boarding schools. This research uses a quantitative approach with the research subjects being Islamic boarding school-based junior high school students in Garut, Tasikmalaya Regency and City, West Java, Indonesia. The sample used was 161 students consisting of 63 students from class 1, 57 people from class 2 and 41 people from class 3 MTs (Junior High schools). Data analysis used the Multivariate Analysis of Variance (Manova). The results of the analysis show that there is a significant effect between parents' educational background on the ability to learn Mathematics, Indonesian and Arabic. Meanwhile, for English and science subjects, parents' educational background does not have a significant effect. Even though there is no effect, in general the educational background of bachelor’s parents has a better comparison across all subjects. Differences appear in the subjects of English, Science, Mathematics and Indonesian, where the junior high school education background is much better than the high school education. Meanwhile, for Arabic subjects, the results of the analysis show that the educational background of elementary school parents is better than high school.